(untitled) (Research, Society and Development, 2022)
An endo-periodontal lesion can be defined as a pathology that damages both periodontal and endodontic tissue of the same tooth. Thus, from a broad understanding of the etiological factors of these lesions, as well as knowledge of the communication routes between both tissues, the professional will be able to perform a good endodontic and periodontal diagnosis, and a satisfactory treatment. Thus, the present study aimed to report the main diagnostic methods used for endo-periodontal lesions, and the most viable therapy options for each specific case of the disease. A bibliographic survey was carried out in Pubmed, LILACS and Scielo databases, in order to select articles relevant to the topic. From the review, it is concluded that the safest way to avoid misdiagnosis and inadequate decision-making in the face of these lesions is an in-depth study of their etiological agents, the understanding of their various types and the knowledge of the pathways that communicate tissue. pulp and periodontal.